2019
DOI: 10.1021/acsami.9b13109
|View full text |Cite
|
Sign up to set email alerts
|

Fast Response Characteristics of Flexible Ultraviolet Photosensors with GaN Nanowires and Graphene

Abstract: We report the fast response characteristics of flexible ultraviolet photosensors with GaN nanowires (NWs) and a graphene channel. The GaN NWs used as light-absorbing media are horizontally and randomly embedded in a graphene sandwich structure in which the number of bottom graphene layers is varied from zero to three and the top is a fixed single layer of graphene. In the response curve of the photosensor with a double-layer bottom graphene, as obtained under pulsed illumination with a pulse width of 50 ms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 68 publications
3
29
0
Order By: Relevance
“…Furthermore, the detecting efficiency at the NIR range is rather distinguished as well, as implied by the excellent data of R (290–570 A W –1 ) and D * (0.5–0.96) × 10 12 Jones). The achieved R and D * at the UV and NIR range stand out remarkably from those of previous reports, and their values for the visible lights are among the top levels of the former studies as well, as can be seen from the top ,,, and bottom parts ,, of Figures f or S2d (detailed photodetecting materials in the cited references provided).…”
Section: Results and Discussionsupporting
confidence: 87%
“…Furthermore, the detecting efficiency at the NIR range is rather distinguished as well, as implied by the excellent data of R (290–570 A W –1 ) and D * (0.5–0.96) × 10 12 Jones). The achieved R and D * at the UV and NIR range stand out remarkably from those of previous reports, and their values for the visible lights are among the top levels of the former studies as well, as can be seen from the top ,,, and bottom parts ,, of Figures f or S2d (detailed photodetecting materials in the cited references provided).…”
Section: Results and Discussionsupporting
confidence: 87%
“…The rise times (decay times) at the light intensity of 10, 20, 40, 60, and 80 mW/cm 2 were calculated to be 75.28 (135.25), 75.30 (135.33), 75.63 (135.53), 75.88 (135.71), and 75.99 ms (136.03 ms), respectively. The rise and decay times were defined as the time required for the current transition from 10 to 90% and from 90 to 10% of the steady-state photocurrent, respectively . The rise and decay times were slightly increased with increasing the light intensity because of the effect of thermal energy caused by incident light …”
Section: Resultsmentioning
confidence: 99%
“…30 Han et al reported highly efficient flexible photosensors with GaN NWs as light-absorbing media. 32,33 However, no stretchable photosensor using the III-nitride material system has been reported, largely due to its intrinsically brittle and rigid characteristics.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Flexible optoelectronic devices provide many novel functionalities and have the potential to open up a new branch of industry. As another novel application, transparent devices have attracted considerable interest as next-generation display technology in various fields, including wearable intelligent electronics, automobile windshield navigation, and IoT (Internet of Things) applications. Because of the extraordinary characteristics of low power consumption, being nontoxic, long lifetime, and high efficiency, GaN-based optoelectronic devices, e.g., light-emitting devices (LEDs), are promising for the above fields. , In addition, this material is also attractive for piezoelectric devices, such as piezoelectric sensors and piezoelectric transistors. Thus, achieving flexible and transparent GaN-based films is a decisive step for future markets and applications. Over the past few years, the fabrication of flexible devices based on thin-film and micropyramid GaN-based materials has been intensively studied by developing procedures to transfer the epitaxial structures from the original rigid substrates used for growth to soft substrates. , These additional procedures usually require laser lift-off or selective wet etching of a thick sacrificial layer or the entire source substrate. , However, besides expensive laser equipment, the laser lift-off technology requires the bandgap of substrate should be larger than that of GaN, which limits its applications. , Furthermore, the sacrificial layers are normally thick, e.g., 2.5 μm in ref , or may need to be highly doped, which can increase the epitaxial cost and deteriorate the epitaxial quality.…”
Section: Introductionmentioning
confidence: 99%